The whispers [large type] - Audrain, Ashley, 1982- (Random House Large Print, 2023)
"The Loverlys sit by the hospital bed of their young son who is in a coma after falling from his bedroom window in the middle of the night; his mother, Whitney, will not speak to anyone. Back home, their friends and neighbors are left in shock, each confronting their own role in the events that led up to what happened that terrible night: the warm, altruistic Parks who are the Loverlys' best friends; the young, ambitious Goldsmiths who are struggling to start a family of their own; and the quiet, elderly Portuguese couple who care for their adult son with a developmental disability, and who pass the long days on the front porch, watching their neighbors go about their busy lives. The story spins out over the course of one week, in the alternating voices of the women in each family as they are forced to face the secrets within the walls of their own homes, and the uncomfortable truths that connect them all to one another. Set against the heartwrenching drama of what will happen to Xavier, who hangs between death and life, or a life changed forever, THE WHISPERS is a novel about what happens when we put our needs ahead of our children's. Exploring the quiet sacrifices of motherhood, the intuitions that we silence, the complexities of our closest friendships, and the danger of envy, this is a novel about the reverberations of life's most difficult decisions." --